Ultrasonography and Computed Tomographic Manifestations of Abdominal Sarcoidosis in Children. Issue 2 (August 2016) - Morel, Baptiste; Sileo, Chiara; Epaud, Ralph; Blondiaux, Eléonore; Nathan, Nadia; Corvol, Harriet; Tounian, Patrick; Le Pointe, Hubert Ducou
ABSTRACT: Objectives: Sarcoidosis is a multisystem, granulomatous inflammatory disease affecting both pediatric and adult patients. So far in children, very few radiological descriptions of abdominal sarcoidosis manifestations have been reported. The present study describes the frequency and the appearance of abdominal radiologic manifestations in pediatric patients with histologically proven sarcoidosis. Methods: We reviewed retrospectively all of the radiological examinations of 22 patients ages 1 to 15 years at diagnosis with proven sarcoidosis evaluated in a university pediatric hospital between 1994 and 2014. The locations of biopsies and the angiotensin-converting enzyme level were reported. The size, shape, and parenchymal homogeneity of the liver and spleen, the presence of abdominal lymph nodes, and abnormalities of the gastrointestinal tract were tabulated. Results: The study included 22 children (mean age: 9.9 ± 2.8 years). The liver was the most frequent location of biopsy (12/22), even without radiological involvement. Abdominal manifestations were present in 11 of 22 children with sarcoidosis. Hepatomegaly was the most frequent abnormality, reported in 8 of 11 cases either homogeneous (n = 7) or nodular (n = 1). Homogeneous lymph node enlargement was noted in 6 of 11 cases and splenomegaly in 4 of 11 cases. No calcification was observed. All patients with initial abdominal sarcoidosis had simultaneous thoracic involvement. Conclusions: Abdominal manifestations in children sarcoidosis are frequent but often nonspecific. Nodular hepatosplenomegaly is rare. All of our patients with abdominal abnormalities had a more specific associated thoracic involvement. Awareness of this association could assist the clinicians in assessing the initial diagnosis of abdominal sarcoidosis in children.